Teacher–Student Sexual Relationships: The Role of Age, Gender, and Multiple Victims on Incarceration and Registration Outcomes - Knoche, Victoria A. (Journal of interpersonal violence, 2021)
Minimal research has examined sentencing outcomes in teacher–student sexual abuse cases, while the research that has been conducted has primarily focused on gender and attractiveness. Furthermore, the body of literature examining how gender affects sentencing has contradictory findings. Age of the victim and number of victims may also play a role in sentencing outcomes. The current study aimed to better understand which factors (by examining how gender of the victim and defendant, age of the victim and defendant, and having multiple victims) are associated with sentencing outcomes in cases where teachers engage in inappropriate sexual relationships with students. The sentencing outcomes that were assessed include length of incarceration, likelihood of having to register as a sexual offender, and likelihood of being incarcerated. The current study reviewed 250 cases that were covered in the media between 2008 and 2010 that involved a defendant who was accused of sexual contact with a student whom they had contact with through their role as an educator or school staff member. Results indicate that defendant age, victim age, and whether there was one or multiple victims had significant implications for sentencing outcomes. An increase in victim age was associated with a decreased likelihood of incarceration, shorter incarceration lengths, and a decreased likelihood to be required to register as a sexual offender. An increase in defendant age was also associated with increased likelihood of incarceration. Furthermore, having multiple victims was associated with increased incarceration lengths. This study has implications for school policies and teacher training specific to building appropriate relationships and boundaries with students. Given the rise in reporting of sexual abuse cases between teachers and their students, implementing more comprehensive ethics training is paramount.